Photon-Upconversion Barcoding with Multiple Barcode Channels: Application for Droplet Microfluidics - Hlaváček, Antonín; Křivánková, Jana; Přikryl, Jan; Foret, František (Analytical chemistry, 2019)
Barcoding facilitates high-throughput analytical methods in complex matrixes with a reduced volume of sample, reagents, time, and cost. Because of orthogonality to fluorescence, photon-upconversion barcodes attracted considerable attention in recent years. We constructed an epiluminescence detector, which, for the first time, demonstrated the reading of photon-upconversion spectra from microdroplets in a microfluidic chip with frequency up to 10 Hz. Non-negative least-squares deconvolution enabled the reading of an unprecedented number of photon-upconversion barcode channels (six) from emission spectra (excitation 980 nm, emission 430-875 nm). The standard deviation of barcode reading from microdroplets was ∼1%. Described barcoding can be, for example, used for multiparameter titrations, multiplexed biological and chemical assays, optimizations on a microfluidic platform, and preparation of barcoded concentration gradients and libraries.